In Hot Arid Region... Kinnow growing fetches more - Sharma, B D; Kumar, R (Indian Horticulture, 2019)
The kinnow has emerged as one of the most economically-viable crop for arid farmers to diversify from the traditional farming and to achieve nutrition and income security. The distinctive agroclimatic conditions of the region particularly high sunshine hours and low humidity impart unique quality (colour, taste and flavour) to kinnow fruits. Adaptability to arid environment, high yield, better quality, rootstock adoptability, low incidence of insects, pest and diseases, tolerance to abiotic stresses, available irrigation facilities, value addition, long productive life for sustainable production and cheap labour availability make it choicest crop of hot arid region. However, hot arid ecosystem is highly fragile and is prone to climate vagaries like high temperature, high wind velocity, high solar radiation, saline soils and low temperatures during winter which adversely affect the kinnow cultivation. Farmers are not able to use the water resource efficiently for better crop production owing to traditional farming system and lack of awareness about efficient, non-availability of adaptable cultivars and technologies. Adoption of micro-irrigation system is desirable to save water and enhance productivity. The weak storage and processing infrastructure results in significant post harvest losses and hence needs to be strengthened.